Deployment of vehicular networks in highways using 802.11p and IPv6 technologies. (2017) - Santa, José; FernÁ¡ndez, Pedro J.; PereÁ±íguez, Fernando
Most of the previous and current vehicular communication deployments, testbeds and, in general, experimental efforts come from research contributions evaluating particular solutions in the area. We have had to wait until recent days to see great testing campaigns in vehicular cooperative systems, coming from research projects supported by national or international funding. This paper reviews the deployment and operation of communication infrastructures in one of the major European projects in this area, i.e., European field operational test on safe, intelligent and sustainable road operation (FOTsis). A key advance of FOTsis has been the integration of IEEE 802.11p and IPv6 technologies following the ISO/ETSI guidelines in cooperative systems for vehicle to infrastructure (V2I) communications. This work reports our main findings providing an interoperable IPv6 access to vehicular services, describes the main test-sites, provides vehicular network performance tests, and summarises our experience in these deployments. Our recommendations pave the way for future large-scale vehicular communication deployments in the V2I segment, which is expected to be the most relevant in the short and medium term.